Mathematical modeling and characteristics of automotive electric power steering systems: A state–of–the–art literature review - Tuan Anh Nguyen (Ain Shams Engineering Journal, 2025)
Electric Power Steering (EPS) systems offer several advantages over traditional steering mechanisms and are increasingly adopted in modern vehicles. The performance of an EPS system strongly depends on its assisted steering characteristic curves, which serve as reference signals for control algorithms. While many models and methods have been proposed to describe and analyze EPS systems, no comprehensive publication has systematically categorized and reviewed the dynamic models and assisted steering characteristics of these systems. This article addresses the research gap by presenting a thorough, up-to-date overview of automotive EPS systems. Specifically, we summarize and compare widely used EPS configurations’ structures, mathematical models, and application scopes. A key contribution of this work is the classification and analysis of various assisted steering characteristic curves, which are essential for optimizing control performance. These curves provide a helpful basis for researchers and engineers in designing optimal EPS system behaviors. To enhance practical accessibility, we also provide a summary table consolidating the main findings, allowing practitioners to reference the characteristics and models discussed quickly. This work’s distinctive contribution is its comprehensive integration of structural and performance-related features of EPS systems.